Parameter Analysis on Hardening Soil Model of Soft Soil for Foundation Pits Based on Shear Rates in Shenzhen Bay, China. (18th February 2020) - Fu, Yanbin; He, Siyue; Zhang, Sizhan; Yang, Yong
Abstract : The hardening soil (HS) model is the most commonly used constitutive models of soft soil of foundation pits of PLAXIS software in numerical analysis, and its parameters are prerequisite for accurate calculation. In this paper, relevant parameters of the HS model in Shenzhen Bay in China were studied through one-dimensional consolidation tests and triaxial shear tests. Analytical methods of reference secant stiffness and failure ratio of soft soil were systematically studied, the influence of shear rates on reference secant stiffness and failure ratio of soft soil was analyzed, and the relationship between stiffness parameters and compressive modulus of soft soil was established. The results showed that reference secant stiffness and failure ratio of soft soil obtained by different analytical methods were quite different, and the errors of reference secant stiffness and failure ratio of soft soil obtained by stress-strain curves were the smallest and the stability was the best; at the same time, with increase of shear rates, the peak deviator stress and reference secant stiffness of soft soil increased, but failure ratio did not change much. The research results could provide a reference of parameter analysis of soft soil for the HS model in the numerical analysis and similar working conditions of foundation pits.